A fruitful alliance: the synergy between Atopobium vaginae and Gardnerella vaginalis in bacterial vaginosis-associated biofilm. (10th March 2016) - Hardy, Liselotte; Jespers, Vicky; Abdellati, Said; De Baetselier, Irith; Mwambarangwe, Lambert; Musengamana, Viateur; van de Wijgert, Janneke; Vaneechoutte, Mario; Crucitti, Tania
Abstract : Objectives: Bacterial vaginosis (BV) is characterised by a change in the microbial composition of the vagina. The BV-associated organisms outnumber the health-associated Lactobacillus species and form a polymicrobial biofilm on the vaginal epithelium, possibly explaining the difficulties with antibiotic treatment. A better understanding of vaginal biofilm with emphasis on Atopobium vaginae and Gardnerella vaginalis may contribute to a better diagnosis and treatment of BV. Methods: To this purpose, we evaluated the association between the presence of both bacteria by fluorescence in situ hybridisation (FISH) and BV by Nugent scoring in 463 vaginal slides of 120 participants participating in a clinical trial in Rwanda. Results: A bacterial biofilm was detected in half of the samples using a universal bacterial probe. The biofilm contained A. vaginae in 54.1% and G. vaginalis in 82.0% of the samples. A. vaginae was accompanied by G. vaginalis in 99.5% of samples. The odds of having a Nugent score above 4 were increased for samples with dispersed G. vaginalis and/or A. vaginae present (OR 4.5; CI 2 to 10.3). The probability of having a high Nugent score was even higher when a combination of adherent G. vaginalis and dispersed A. vaginae was visualised (OR 75.6; CI 13.3 to 429.5) and highest when both bacteria were part of the biofilm (OR 119; CI 39.9 to 360.8). Conclusions: Our study, although not comprehensive at studying the polymicrobial biofilm in BV, provided a strong indication towards the importance of A. vaginae and the symbiosis of A. vaginae and G. vaginalis in this biofilm. Trial registration number: NCT01796613.